AB0434 Association between cardiovascular events and classic cardiovascular risk factors and disease characteristics in patients with rheumatoid arthritis. (23rd January 2014) - Gil, S.; del Olmo, L.; García, S.; Alcocer, P.; Lojo, L.; Plasencia, C.; Bonilla, M.G.; Balsa, A.; Martin-Mola, E.
Abstract : Objectives: To estimate the prevalence of cardiovascular events (ischemic heart disease, heart failure, stroke and peripheral artery disease) in patients with rheumatoid arthritis (RA) and the association with classic cardiovascular risk factors and disease characteristics such as bone erosions, extra-articular manifestations and the presence of anti-citrullinated peptide antibodies (ACPA) and Rheumatoid Factor (RF). Methods: An observational retrospective study was performed on 306 patients diagnosed with Rheumatoid Arthritis. A questionnarie was designed which was filled out at routine visits to the rheumatology clinic in which we assesed the date of RA diagnosis, cardiovascular events, classic cardiovascular risk factors, RA clinical characteristics and concomitant treatments. Results: our cohort included 306 patients, 229 (74.8%) women, mean age 63.1±13.3 years. In our study, 234 (76.5%) patients were positive for RF and 229 (74.8%) for ACPA, 192 (62.7%) had bone erosions and 55 (18.0%) extra-articular manifestations. Cardiovascular events occurred in 52 (17.0%) patients, most (34 cases, 65.3%) after the diagnosis of RA; 4 patients (7.6%) had an stroke, 4 (7.6%) peripheral artery disease, 14 (26.9%) heart failure and 30 (57.6%) acute myocardial infarction. Cardiovascular events appeared more frequently in patients with high blood pressure [OR 9.1; (95% CI 4.2-19.5; p <0.001)], diabetes mellitus [OR 2.9; 95% CI 1.4-5.9; p 0.003)], hypercholesterolemia [OR 2.5; 95% CI 1.3-4.7; p 0.003)] and hypertriglyceridemia [OR 3.4; 95% CI 1.7-6.8; p 0.001)]. We observed higher frequency of cardiovascular events in patients who had bone erosions [OR 1.9; 95% CI 0.9-3.9; p 0.07] and in those with extra-articular manifestations [OR 1.9; 95% CI 0.9-3.9; p 0.07]. Conclusions: Classic cardiovascular risk factors have a high prevalence in patients with RA. The most frequent cardiovascular event was ischemic heart disease. In our study, we observed that there is a correlation between the presence of classic cardiovascular risk factors and cardiovascular events. There is a greater number of cardiovascular events in patients with bone erosions and RA extra-articular manifestations than in patients without these characteristics, though the difference was not statistically significant. Disclosure of Interest: None Declared